Comparison between Ayrshire, Friesian and Finnish cattle dairy cows on home - produced feeds - Ettala, Elsi (Agricultural and Food Science, 1983)
An experiment with Ayrshire(Ay), Friesian (Fr) and Finnish cattle(Fc) animals on home produced feeds under same kind of conditions is conducted at North Savo Experimental Station in the years 1979-87. The test animals (40 Ay, 40 Fr, 16 Fc) was taken by random sampling when they were calves. One half of the animals of each race receives silage-grain feeding, the other half hay-grain-urea feeding. The growth rate of the calves was equal in the beginning but later on the Friesian animals grew fastest and the Finnish cattle animals most slowly. The average milk yield of the first lactation year was at the same level in the Friesian groups and in the Ayrshire hay-group. The first milk yield of the Ayrshire silage-group was a little lower than of those mentioned before and clearly lower in the Finnish cattle groups. The milk yields were a consequence of the feed consumptions of the animals. In the second lactation year the feed consumptions and the milk yields have increased distinctly. There are not to be found differences in the conception rates depending on races.